Time-resolved study of recoil-induced rotation by X-ray pump – X-ray probe spectroscopy. Issue 11 (2nd March 2022) - Liu, Ji-Cai; Ignatova, Nina; Kimberg, Victor; Krasnov, Pavel; Föhlisch, Alexander; Simon, Marc; Gel'mukhanov, Faris
Abstract : We propose two color X-ray pump–probe spectroscopy, which opens new perspectives in studies of molecular rotational dynamics induces by the recoil effect in real-time. The feasibility of experimental observation is also discussed. Abstract : Modern stationary X-ray spectroscopy is unable to resolve rotational structure. In the present paper, we propose to use time-resolved two color X-ray pump–probe spectroscopy with picosecond resolution for real-time monitoring of the rotational dynamics induced by the recoil effect. The proposed technique consists of two steps. The first short pump X-ray pulse ionizes the valence electron, which transfers angular momentum to the molecule. The second time-delayed short probe X-ray pulse resonantly excites a 1s electron to the created valence hole. Due to the recoil-induced angular momentum the molecule rotates and changes the orientation of transition dipole moment of core-excitation with respect to the transition dipole moment of the valence ionization, which results in a temporal modulation of the probe X-ray absorption as a function of the delay time between the pulses. We developed an accurate theory of the X-ray pump–probe spectroscopy of the recoil-induced rotation and study how the energy of the photoelectron and thermal dephasing affect the structure of the time-dependent X-ray absorption using the CO molecule as a case-study. We also discuss the feasibility of experimental observation of our theoretical findings, opening new perspectives in studies of molecular rotational dynamics.